PENGETAHUAN, SIKAP DAN PRAKTIK MASYARAKAT KECAMATAN KINTAMANI TERHADAP PENGGUNAAN OBAT TRADISIONAL - Dewi Puspita Apsari; Ni Putu Wintariani (LPPM Akafarma Sunan Giri Ponorogo, 2022)
Background: Complementary Alternative Medicine (CAM) is very popular among people. Nevertheless, an inappropriate combination of CAM and conventional medicine can lead to adverse drug reactions (ADR). This is very limited known by the public. Therefore, it is necessary to conduct research on the knowledge, attitudes, and practices of using CAM in Kintamani District. Methods: This cross-sectional quantitative study was conducted from June to Agustus 2021. The target population in this study was 102 people in Kintamani District who were more than or equal to 18 years old and using CAM maximum of a year before. Descriptive data were processed using SPSS (21.0) to describe the knowledge, attitudes, and practices of CAM. Pearson correlation test was conducted to determine the relationship between demographic characteristics on knowledge and attitudes to use CAM. Results: The level of knowledge Kintamani District regarding the use of CAM is sufficient as many as 71 (69.61%) people. In addition, 95 (93%) people have a positive attitude about using CAM. In practice, 44 (42.3%) people use herbs in the category of CAM that is often used. Information about CAM they got from the family was 37 (29.6%) and was used to treat hypertension as many as 35 (32.8%) respondents. Conclusion: People in Kintamani District, Bangli have sufficient knowledge and a positive attitude towards the use of CAM. In addition, most people use traditional medicine to treat hypertension